2020
DOI: 10.1371/journal.pcbi.1007965
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of three-dimensional sinusoidal networks in liver tissue

Abstract: Can three-dimensional, microvasculature networks still ensure blood supply if individual links fail? We address this question in the sinusoidal network, a plexus-like microvasculature network, which transports nutrient-rich blood to every hepatocyte in liver tissue, by building on recent advances in high-resolution imaging and digital reconstruction of adult mice liver tissue. We find that the topology of the three-dimensional sinusoidal network reflects its two design requirements of a space-filling network t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 58 publications
(127 reference statements)
1
23
0
Order By: Relevance
“…The liver is the largest internal organ and controls organism metabolism [ 42 ]. Myostatin inhibits proliferation and insulin-stimulated glucose uptake in liver cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the largest internal organ and controls organism metabolism [ 42 ]. Myostatin inhibits proliferation and insulin-stimulated glucose uptake in liver cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We can analyze nematic order of cell polarity not only within an ensemble of cells, but also quantify the mutual alignment between cell polarity and auxiliary anisotropic structures such as transport networks. As example, we analyze co-orientational order between apical nematic cell polarity of hepatocytes, and the local anisotropy of the blood-transporting sinusoidal network [ 15 , 26 ]. Sinusoids are specialized blood vessels forming a network within the liver lobule [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found co-alignment between nematic cell polarity of hepatocytes and the local anisotropy of the sinusoidal network. This mutual alignment is not uniaxial, but of phase-biaxial type, i.e., its description requires two reference axes, a preferred axis of the sinusoidal network (approximately parallel to the direction of blood flow [ 26 , 34 ]), and a plane axis, which characterizes local layered order of the sinusoidal network. Specifically, we observe signatures of layered organization of the sinusoidal network, characterized by a distinguished plane axis ( s 2 ), normal to layers enriched in sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…and subsequently the local Peclet numbers. The impact of the simultaneously given dissipation-volume constraints, as in (16), is tuned via the coupling parameters α 0 , α 1 . Increased volume penalties α 0 naturally lead to smaller vessel structures, simultaneously increasing P e and therefore hindering solute uptake.…”
Section: Multi-target Driven Radius Optimizationmentioning
confidence: 99%
“…A recurring problem in these studies is to identify stimuli causing the complex topology of capillary networks, i.e. resilient, space-filling meshes containing hydrodynamically favorable 'highways', defying Murray's law [16][17][18]. Subsequently, more complex stimuli such as growth, noisy flow patterns and hemodynamical complications have been rigorously discussed in computational studies, and have been found to account for complex topological changes in the respective networks [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%